1984
DOI: 10.1085/jgp.83.2.287
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among intracellular sodium activity, calcium, and strophanthidin inotropy in canine cardiac Purkinje fibers.

Abstract: The role of sodium and calcium ions in strophanthidin inotropy was studied by measuring simultaneously the electrical, mechanical, and intracellular sodium ion activities in electrically driven cardiac Purkinje fibers under conditions that change the intracellular sodium or calcium level (tetrodotoxin, strophanthidin, high calcium, and norepinephrine) . Tetrodotoxin (TTX ; 1-5 X 10 -s M) shifted the action potential plateau to more negative values, shortened the action potential duration, and decreased the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…Ouabain has been thought to increase the contraction through a Na+-Ca2+ exchange mechanism (Reuter & Seitz, 1968;Sheu & Fozzard, 1982;Wasserstrom et al, 1983;Eisner et al, 1984;Vassalle & Lee, 1984;Wier & Hess, 1984;Grupp et al, 1985). Ouabain inhibits Na'-K' ATPase and results in an accumulation of [NaJ]i.…”
Section: Discussionmentioning
confidence: 99%
“…Ouabain has been thought to increase the contraction through a Na+-Ca2+ exchange mechanism (Reuter & Seitz, 1968;Sheu & Fozzard, 1982;Wasserstrom et al, 1983;Eisner et al, 1984;Vassalle & Lee, 1984;Wier & Hess, 1984;Grupp et al, 1985). Ouabain inhibits Na'-K' ATPase and results in an accumulation of [NaJ]i.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with this increase in the aia there was an increase in the active tension, and calcium activity (Lee et al 1982;Vassalle & Lee, 1984). Calculation of the sodium activity gradient showed that the sodium driving force decreased significantly during the exposure to ouabain.…”
Section: Discussionmentioning
confidence: 99%
“…The preparations were driven at 60 min-' and the stimuli were delivered by a Grass stimulator (model S-4) through a Grass stimulus isolation unit (SIU 4678 (Lee, 1981;Lee & Vassalle, 1983;Vassalle & Lee, 1984). The signals from the Na+ selective and conventional microelectrodes were filtered by means of identical low pass filters (with a fixed frequency of 0.24 Hz) .…”
Section: Methodsmentioning
confidence: 99%
“…Lee & Vassalle, 1983): the increased Na gradient across the sarcolemma decreases [Ca]i via the Na/Ca exchange. In Table IA Tetrodotoxin (TTX) lowers aiNa (see Vassalle & Lee, 1984) and therefore [Ca]i: force decreases when aiNa decreases (Abete & Vassalle, 1987). In Table IB [Ca].…”
Section: Methodsmentioning
confidence: 99%